ISOLATION AND CHARACTERIZATION OF FLAVONOID COMPOUNDS FROM ETHYL ACETATE FRACTION OF Macaranga lamellata Whitmore LEAVES - Sherly Indah Puspita; Eva Marliana; Daniel Daniel (Jurusan Kimia FMIPA UNMUL, 2019)
Isolation and characterization of flavonoid compounds from ethyl acetate fraction of Macaranga lamellata Whitmore leaves have been done in this research. Macaranga lamellata Whitmore leaves was macerated using methanol and fractionated with n-hexane and ethyl acetate. The separation process of ethyl acetate fraction was conducted using gravity column chromatography by Step Gradient Polarity (SGP) method. The isolate was tested for its purity using thin layer chromatography with various eluents i.e. n-hexane, chloroform, methanol, acetone and ethyl acetate, with Rf values were 0; 0,7857; 0,8333; 0,9048 and 0,9286 respectively. The result indicated that the isolate was obtained as ML1 (3 mg) belong to flavonoid compound in the form of oil. Analysis of ML1 compound using UV displayed 2 peaks at ? 291 nm (band II) and 342 nm (band I). Analysis of ML1 compound using FT-IR displayed functional groups -OH, C-H aromatic, C-H aliphatic, C=C aromatic, C=O, C-OH and C-O-C. Based on the results of UV and FT-IR spectra, ML1 compound was suspected to contain flavonoid compound.